If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+6)+(3x-4)=37
We move all terms to the left:
(2x+6)+(3x-4)-(37)=0
We get rid of parentheses
2x+3x+6-4-37=0
We add all the numbers together, and all the variables
5x-35=0
We move all terms containing x to the left, all other terms to the right
5x=35
x=35/5
x=7
| -3/2+2/7v=-4/3 | | 5m²+20m=0 | | 4/5s-1/5s=9 | | (2x-15)=50 | | 0.4=(x-28.3)/x | | x+(2/3)*x+(4/9)*x=76 | | 7/x=21/25 | | 3(3)-2y=15 | | 0.4=(x-975800)/x | | 8×+1/7=9x+4/7 | | (n+3)(9-5)=16 | | 0.4x=x-975800 | | 4a-7a=-56 | | 4x/9=76 | | 180=(6x+20)+2x+4 | | 4*s+9=12s | | (9+8i)(9-8i)=0 | | 6x+3=64 | | 2x+10-15+15x=10 | | x2-10/x-1=-14-5x/x-1 | | (3z+3)/2=(z+3)/4 | | 0.9=4.2/x | | 13+8x-8=5x+10 | | 12x+3x²=63 | | y=110(1.07)^4 | | (-7+3i)(9+i)=0 | | 7i(5-2i)=0 | | 1/x+2/7=19/42 | | 4(t-2)+4=(2t-5) | | 10t=7t-9 | | 5m(5m+6)=9 | | 2x^+2x=0 |